Analisa Strategi Pengembangan Bisnis PT Tanabe Indonesia Dalam Mengahadapi Era Jaminan Kesehatan Nasional - Midyan Aji Arso (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This research was conducted to analyze the business development strategy of PT Tanabe Indonesia in the face of the JKN era, by describing the internal conditions such as Marketing, Finance, production and human resources and also external condition of companies, namely the five-force analysis. Then a SWOT analysis is performed to identify the strengths, weaknesses, opportunities and threats. The study was conducted with a qualitative-descriptive method using primary and secondary data collection techniques through interviews, observation and identification of company documents. From the results of the study it was concluded that the business development strategy in facing the JKN era carried out by PT Tanabe Indonesia was a focus strategy, namely focusing the company on narrower market segments and maintaining production efficiency and effectiveness.